Methods of surgical treatment of glioblastoma multiforme, its implications for survival and functional post operative condition - Diez Pinge, Christian Xavier (Revista Universidad de Guayaquil, 2014)
Glioblastoma multiforme is a type of malignant glioma comprising about 25 to 30% of primary brain tumors. Despite significant advances in our understanding of the basis of tumor pathogenesis, the median survival of these patients has increased only 3.3 months in the last 25 years. At diagnosis, the treatment is surgical resection as radical as possible followed by radiotherapy. Chemotherapy regimens have recently been added to the therapeutic arsenal, which has been made a small increase in survival. In this article we review various surgical treatment modalities and their implications in improving survival in this group of patients.
Keywords: Malignant glioma; Progression free survival; complete resection; Freedom